The Maltese falcon - Huston, John (Santa Monica, CA MGM/UA Home Video, 1941)
Who murdered Miles Archer? No one knows. But what Archer's partner, Private Eye Sam Spade, does know is that Archer was killed while investigating the disappearance of a priceless statue...and now Spade has three mysterious clients who want to find it-at any cost.
Based on the novel by Dashiell Hammett.
Executive producer, Hal B. Wallis ; Associate producer, Henry Blanke ; Screenplay by John Husto.
Humphrey Bogart, Mary Astor, Dashiell Hammet, Gladys George, Peter Lorre, Barton MacLane, Lee Patrick, Sydney Greenstreet.
VHS format.
In English.
Keywords: American fiction -- 20th century -- Film and video adaptations; Detective and mystery films; Feature films